Contribution of the co.LAB Framework to the Collaborative Design of Serious Games: Mixed Methods Validation Study - Dominique Jaccard; Laurent Suppan; Félicia Bielser (JMIR Publications, 2021)
BackgroundMultidisciplinary collaboration is essential to the successful development of serious games, albeit difficult to achieve. In a previous study, the co.LAB serious game design framework was created to support collaboration within serious game multidisciplinary design teams. Its use has not yet been validated in a real usage context. ObjectiveThe objective of this study was to perform a first assessment of the impact of the co.LAB framework on collaboration within multidisciplinary teams during serious game design and development. MethodsA mixed methods study was conducted, based on 2 serious game design projects in which the co.LAB framework was used. The first phase was qualitative and carried out using a general inductive approach. To this end, all members of the first serious game project team who used the co.LAB framework were invited to take part in a focus group session (n=6). In a second phase, results inferred from qualitative data were used to define a quantitative instrument (questionnaire) that was designed according to the Checklist for Reporting Results of Internet E-Surveys. Members of both project teams (n=11) were then asked to answer the questionnaire. Quantitative results were reported as median (Q1, Q3), and appropriate nonparametric tests were used to assess between-group differences. Finally, results gathered through the qualitative and quantitative phases were integrated. ResultsIn both phases, the participation rate was 100% (6/6 and 11/11). Verbatim transcripts were classified into 4 high level themes: (1) influence on collaborative dimensions; (2) impact on project course, monitoring, and efficiency; (3) qualitative perceptions of the framework; and (4) influence of team composition on the use of the framework. The web-based questionnaire was then developed according to the 7 dimensions of collaboration by Burkhardt et al. In both projects, the co.LAB framework had a positive impact on most dimensions of collaboration during the multidisciplinary design and development of serious games. When all collaborative dimensions were aggregated, the overall impact of the framework was rated on a scale from -42 to 42 (very negative to very positive). The overall median score was 23 (Q1, Q3: 20, 27), with no significant difference between groups (P=.58). Most respondents also believed that all serious game design teams should include a member possessing significant expertise in serious game design to guide the development process. ConclusionsThe co.LAB framework had a positive impact on collaboration within serious game design and development teams. However, expert guidance seems necessary to maximize development efficiency. Whether such guidance can be provided by means of a collaborative web platform remains to be determined.